Assessment apps to evaluate students’ reading progress in English classroom - Camacho-Minuche, Gina Karina; Ulehlova, Eva; Espinoza-Celi, Verónica (Institute of Advanced Engineering and Science, 2025)
The traditional way to assess students’ reading progress hinders their motivation and engagement, which negatively affects their academic performance. Therefore, this study seeks to address the issue by analyzing the effectiveness of three interactive technological assessment tools: Kahoot, Quizizz, and Socrative, as alternatives for assessing English as foreign language (EFL) students’ reading comprehension, as well as exploring the students’ perceptions about the use of these technological tools. This quasi-experimental study involved mixed method approach and consider 60 senior high school students of Loja, South of Ecuador as a purposive sample. There were outlined advantages and drawbacks linked to three assessment technological tools applied; however, Socrative revealed to be the most effective. Effectiveness seemed contingent upon several variables, such as the educational goals, functionalities of the tools, and the students’ settings. Additionally, the use of technological tools provided a range of resources to enhance dynamism and engagement of learning by facilitating interaction among students. In essence, this resulted in the consolidation of new knowledge, enabling students to retain information over an extended duration.